An Early Oligocene Fossil Lagerstätten from the Lacustrine Deposits of the Luberon UNESCO Global Geopark - Pauline Coster; Stephane Legal (Geoconservation Research)
The Luberon early Oligocene fossil Lagerstätte yields exquisitely well-preserved fossils as testified by the remains of articulated skeletons, skin outlines, feathers and original pigmentation patterns. The fossils include plants, insects, amphibians, reptiles, birds and mammals from ancient lacustrine-terrestrial ecosystems of the early Oligocene. The fossil birds are especially important, including one of the most complete specimens of trogons, an exceptionally preserved almost complete modern-type hummingbird, and one of the earliest fossil passerine birds. This was a time of warm conditions across Europe and other continents following the Eocene-Oligocene extinction event, known as the Grande Coupure. Most other Oligocene Lagerstätten worldwide are late Oligocene in age. The designation of the Luberon Regional Nature Park as a UNESCO Global Geopark has been an important step toward the protection and management of this world-class paleontological heritage along with scientific research and public education.